Evaluate Students' Perceptions of the Virtual Learning Environment at Paisley University - Abbad, Muneer; Al bargothi, Mohamad (International Journal of Emerging Technologies in Learning (iJET), 2011)
The number of students studying online has been dramatically increased. This has brought an interest and encouragement to some researchers to examine and evaluate the values perceived from the online learning, and why these vast amounts of students are joining the online learning. The purpose of this study is dedicated to evaluate the studentsâ?? perception of the e-learning system at Paisley University. This study evaluates several factors influencing the perceptions of the undergraduate students who undertaken the information management course. The outcome of this study shows that online students perceived the values of the e-learning system differently and the factors mentioned in the literature review each of whom has its own effect on their perceptions.